Penggunaan Media Buku Cerita Bergambar dalam Perkembangan Bahasa Anak - Widya Anggraini Selian; Nurhayati Nurhayati; Sariah Sariah (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2019)
This research was instigated by some problems of student language development, so it aimed at knowing the effect of using Story Book with Picture media toward student language development at Group B of Mayang Kindergarten Pekanbaru. It was conducted from June to October 2019 at Mayang Kindergarten Pekanbaru. The subjects of this research were the students. There were two classes that were studied by the researcher—15 students of group B2 as the experimental group and 16 students of group B3 as the control group, and they were 31 students. The object was the effect of using Story Book with Picture media toward student language development at Group B of Mayang Kindergarten Pekanbaru. Observation, documentation, and interview were the techniques of collecting the data. Based on the research findings, the use of Story Book with Picture media could affect student language development, and it was based on the comparison between pretest and posttest of experimental group using t-test. It was obtained that tobserved was 20.051, and Sig. (2-tailed) 0.000. Because Sig. (2-tailed) was lower than 0.05, it could be concluded that there was a significant effect after using Story Book with Picture media toward student language development.  So, it meant that H0 was rejected and Ha was accepted. There was an effect before and after using Story Book with Picture media toward student language development of experimental group. The effect of using Story Book with Picture media toward student language development at Group B of Mayang Kindergarten Pekanbaru was . Keywords: Story Book with Picture Media Use, Language Development